Investigation on the Quality of Commercially Available GABA Tea in Taiwan - Mu-Chen Wu; Shih-Lun Liu; Bo-Kang Liou; Chun-Yeh Chen; Yuh-Shuen Chen (Standards, 2023)
This study collected 220 commercially available samples of γ-Aminobutyric acid (GABA) tea produced in Taiwan from 2016 to 2021. The 220 tea samples were categorized into five types of GABA tea, including 108 GABA Oolong tea, 71 GABA Black tea, 21 GABA Paochong tea, 12 GABA Green tea, and 8 GABA Puerh tea samples. The most common type of GABA tea in Taiwan is GABA Oolong tea, followed by GABA Black tea. The physico-chemical constituents and consumer acceptance of the GABA tea samples were analyzed. The GABA content varied among the different types of GABA tea: GABA Oolong tea ranged from 128–286 mg/100 g, GABA Black tea ranged from 182–360 mg/100 g, GABA Paochong tea ranged from 98–203 mg/100 g, GABA Green tea ranged from 56–174 mg/100 g, and GABA Puerh tea ranged from 142–191 mg/100 g. In terms of the commercial standard of GABA tea, 22 out of the 220 GABA tea samples failed to meet the commercial standard, with a failure rate of 10%. During the fermentation process of GABA tea, the contents of GABA increased significantly, but the total polyphenol and total catechin contents remained stable. In terms of consumer acceptance, GABA Black tea is the most accepted by consumers, followed by GABA Puerh tea, GABA Paochong, and GABA Oolong tea. The sour flavor in GABA tea is similar to the original sour sensory properties found in black tea. It is assumed that this is the main reason GABA Black tea has the highest acceptance.